2013
DOI: 10.1097/jsm.0b013e318281f09f
|View full text |Cite
|
Sign up to set email alerts
|

Preseason Reports of Neck Pain, Dizziness, and Headache as Risk Factors for Concussion in Male Youth Ice Hockey Players

Abstract: Baseline testing may be of benefit to identify individuals with symptoms of dizziness, neck pain, and headaches who may be at a higher risk of concussion during the season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 39 publications
2
49
0
2
Order By: Relevance
“…This work persisted with what others have found (e.g., Makdissi et al, 2010;Schneider, Meeuwisse, Kang, Schneider, & Emery, 2013;Weinstein et al, 2013), suggesting that headache remains a concerning indicator of concussion, holding that the symptom surfaces shortly thereafter (Stovner, Schrader, Mickevičiene, Surkiene, & Sand, 2009). Moreover, after Weinstein and colleagues' report, the authors searched the concussion literature concerning headaches, concluding that a "profound ongoing headache may be a more specific predictor [of concussion] than other subjective symptoms" (2013, p. 334).…”
Section: Nature Of Recurrent Concussionsupporting
confidence: 43%
“…This work persisted with what others have found (e.g., Makdissi et al, 2010;Schneider, Meeuwisse, Kang, Schneider, & Emery, 2013;Weinstein et al, 2013), suggesting that headache remains a concerning indicator of concussion, holding that the symptom surfaces shortly thereafter (Stovner, Schrader, Mickevičiene, Surkiene, & Sand, 2009). Moreover, after Weinstein and colleagues' report, the authors searched the concussion literature concerning headaches, concluding that a "profound ongoing headache may be a more specific predictor [of concussion] than other subjective symptoms" (2013, p. 334).…”
Section: Nature Of Recurrent Concussionsupporting
confidence: 43%
“…Four studies reported an increased risk of concussion in junior ice hockey players who had a history of previous concussions 2123 27. Similarly, a greater risk was also observed in rugby union players with one or more than two previous concussions 26.…”
Section: Resultsmentioning
confidence: 94%
“…Aside from the direct biomechanical associations and injury mechanics mentioned in the Introduction, the symptoms of headache and dizziness, so prevalent in concussion-type injuries, may actually be the result of cervicogenic mechanisms due to a concomitant whiplash injury suffered at the same time [22,29,79,80]. Two primary categories of mechanisms can be proposed: pain-related and proprioceptive-related.…”
Section: Case For a Likely Cervicogenic Component To Concussion Injuriesmentioning
confidence: 97%